2016
DOI: 10.1039/c6dt02406h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical design of magnetic wires from acene and nanocorone derivatives

Abstract: Theoretical calculations on a series of molecular models based on amino derivatives of linear and cycled acenes acting as organic linkers between two copper(ii) ions have shown a wire-like magnetic behaviour, so that the intermetallic magnetic communication does not vanish when the linker becomes larger due to its polyradical nature. Hence, these models can be considered as molecular magnetic wires, which can be used as active components for molecular spintronics, where the information transport is based on sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Cano et al have shown the effect of increasing open shell character of acenes escalating the spin contamination in both the triplet and BS states with dinuclear copper(II) systems. [74] Applying ab initio calculations here we have quantified the radicaloid characters (y-value) of the pristine polyacene as well as for polyacene in diradicals 1-10 where it acts as a coupler between -NO radical sites and tabulated in Table 3. This has been calculated following the work of Yamaguchi et al [75].…”
Section: Hubbard-u Corrected Gga + U Functionalmentioning
confidence: 99%
“…Cano et al have shown the effect of increasing open shell character of acenes escalating the spin contamination in both the triplet and BS states with dinuclear copper(II) systems. [74] Applying ab initio calculations here we have quantified the radicaloid characters (y-value) of the pristine polyacene as well as for polyacene in diradicals 1-10 where it acts as a coupler between -NO radical sites and tabulated in Table 3. This has been calculated following the work of Yamaguchi et al [75].…”
Section: Hubbard-u Corrected Gga + U Functionalmentioning
confidence: 99%
“…Cano et al have shown the effect of increasing open shell character of acenes escalating the spin contamination in both the triplet and BS states with dinuclear copper(II) systems. 70 Applying ab initio calculations here we have quantified the radicaloid characters (y-value) of the pristine polyacene as well as for polyacene in diradicals 1-10 where it acts as a coupler between -NO radical sites and tabulated in Table 3. This has been calculated following the work of Yamagucghi et al 71 and details of calculations could be found in SI.…”
Section: Magnetic Exchange Interactions Vs Length Of the Couplersmentioning
confidence: 99%
“…The basic components of a molecular spintronic circuit are molecular magnetic wires (MWs), which would facilitate the magnetic communication between the spin carriers along the circuit [100,101]. MWs offer a new design concept for the transfer of information over long distances based on EE interactions and without current flow [102][103][104][105][106][107][108][109][110][111][112][113][114][115], in contrast to conventional charge transport-based electronic wires [116][117][118][119][120][121][122], as stated by Lloret [100]. Indeed, setting a long-range magnetic coupling between two distant spin centers connected by a long organic spacer that ultimately extends over infinite distances ("wire-like magnetic coupling") is the cornerstone.…”
Section: Dinuclear Copper(ii) Metallacyclophanes In the Proof-of-concmentioning
confidence: 99%